2018
DOI: 10.1002/jsde.12182
|View full text |Cite
|
Sign up to set email alerts
|

Selective Syntheses and Properties of Anionic Surfactants Derived from Isosorbide

Abstract: Two series of anionic surfactants (endo‐5‐O‐alkyl isosorbide‐2‐O‐propyl sulfonic acid sodium salt and exo‐2‐O‐alkyl isosorbide‐5‐O‐propyl sulfonic acid sodium salt) with straight alkyl chains (hexyl, octyl, decyl, and dodecyl) were synthesized from isosorbide derived from biomass, through steps of allylation, alkylation, and sulfonation. The selectivity and efficiency of the reactions were optimized by adjusting the solvent, catalyst, reactant molar ratio, and temperature. The product 2‐O‐allyl isosorbide was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Various physicochemical properties such as solubility, foamability, surface tension, and critical micelle concentration (CMC) were determined (Table 3). 24 Since most cleaning formulations are water-based, a high water solubility of the surfactant is desired. 33 The synthesized surfactants with L-Ara and D-GalA contain an alkyl chain length varying from 6 to 12 carbons.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various physicochemical properties such as solubility, foamability, surface tension, and critical micelle concentration (CMC) were determined (Table 3). 24 Since most cleaning formulations are water-based, a high water solubility of the surfactant is desired. 33 The synthesized surfactants with L-Ara and D-GalA contain an alkyl chain length varying from 6 to 12 carbons.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In particular, we found that the tertiary amine surfactants are more soluble in water and display favorable surfactant properties such as foamability, stable foams, and emulsions, lowered surface tension of solutions, and a variable critical micelle concentration. 24,25 Hence, this class of molecules may represent a promising set of biobased surfactants derived from sugar beet pulp.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, its monoethers cannot be considered surfactants. Nevertheless, anionic and cationic isosorbide‐derived surfactants have been recently synthetized (Cho et al, 2018; Parikh et al, 2020). Lauric isosorbide monoethers can be converted into molecules with a more balanced hydrophilic–lipophilic affinity.…”
Section: Building Blocks and Chemicals Derived From Carbohydratesmentioning
confidence: 99%
“…Recently, Cho et al [ 63 ] have proposed a new method for the synthesis of isosorbide-based sulfonate anionic surfactants, with hexyl, octyl, decyl, and dodecyl side chains, in the presence of KOH and toluene or using lithium hydroxide and alkyl bromide in dimethyl sulfoxide.…”
Section: Bio-based Surfactantsmentioning
confidence: 99%